Orofacial manifestations of anemia: characteristics for a dental approach (Research, Society and Development, 2020)
The objective of this study was to investigate in the literature which as oral and facial manifestations of anemias, addressing their etiological characteristics for better dental care in patients with this comorbidity. For this, a narrative review of the literature was carried out with articles published from 2000 to 2020 in the online databases PubMed (National Libary of Medicine) and SciELO (Scientific Electronic Library Online) using the descriptors and synonyms MeSH: "Anemias" in association with "Oral Manifestations". Of the 583 articles, 35 were used in this study. It was observed that the main anemias that presented oral signs were iron deficiency, hemolytic, megaloblastic, sickle cell and thalassemia. It was reported, mainly, the yellowish color in the oral mucosa and skin, as well as periodontitis, bone hyperplasia, osteomyelitis or even the loss of dental vitality from the infarction of local vascularization. Thus, it is extremely important for the dentist to understand the characteristics of this manifestation in order to correctly manage these patients, since some approaches may worsen the anemic picture.